(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article is devoted to the basic categories, conditions of illocutionary acts, types of differences among them and one of the most well-known classifications made by Fraser. Special attention should be paid to the performative hypothesis and types of performatives. The students are to be able to distinguish between performative and constatives utterances. Unlike constatives, that can be true or false, performatives have felicity conditions – a typology of conditions which performative utterances must meet if they are to succeed or be “happy”. It should be made clear that in the utterance of a sentence three kinds of acts are simultaneously performed: locutionary, illocutionary and perlocutionary. It is very important that the conditions of performing illocutionary acts be elucidated and analyzed on numerous examples to be able to use